The anti-inflammatory effects of acetaminophen and N-acetylcysteine through suppression of the NLRP3 inflammasome pathway in LPS-challenged piglet mononuclear phagocytes. Issue 6 (August 2015) - Liu, Yu; Yao, Wenxu; Xu, Jun; Qiu, Yinsheng; Cao, Fangyuan; Li, Sali; Yang, Sheng; Yang, Hailan; Wu, Zhongyuan; Hou, Yongqing
Acetaminophen (AAP) and N -acetylcysteine (NAC) have been found to have anti-inflammatory effects via the TLR–NF-κB pathway in LPS-challenged piglets. However, the action mechanisms employed by AAP and NAC have yet to be completely understood. This study investigated the anti-inflammatory effects and mechanisms of AAP and NAC on LPS-induced inflammatory responses via the NLRP3 inflammasome pathway in piglet mononuclear phagocytes. The results show that mRNA expression levels of IL-1β, IL-18 and NLRP3, as well as the protein level of cleaved caspase-1, are significantly increased after LPS challenge in vitro . LPS stimulation did not change ASC and caspase-1 mRNA levels, which were components of NLRP3 inflammasome complex. AAP (0.5–1.0 mM) and NAC (0.5–1.0 mM) used individually or in combination could down-regulate protein expression of cleaved caspase-1 and mRNA expression of IL-1β, IL-18 and NLRP3. NAC could significantly enhance the above inhibition actions of AAP. The combined use of AAP plus NAC had better inhibition action on the NLRP3 inflammasome pathway. These results indicate that the anti-inflammatory effects of AAP and NAC occur via the regulation on mRNA expression of NLRP3 and activation of caspase-1. The anti-inflammatory activity of AAP and NAC could be related to the suppression of NLRP3 inflammasome pathway under LPS stimulation.